1997
DOI: 10.1097/00005053-199704000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Alexithymia Hypothesis: Physiological and Subjective Responses During Relaxation and Stress

Abstract: Alexithymia has been linked to various disorders, including compulsive behaviors, anxiety disorders, and physical conditions with or without symptoms. It has been hypothesized that these disorders result from the alexithymic inability to differentiate and elaborate affect, which gives rise to physiological arousal and a negative subjective state, which are not regulated by psychological strategies. We tested these hypothesized mechanisms by comparing 42 alexithymic subjects with 42 sex- and race-matched non-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
7

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 27 publications
7
74
0
7
Order By: Relevance
“…This is reflected in findings of poorer bodyperception, such as reduced registration of the effects of chemical intake or poorer perception of own heart beat (Ernst et al 2014;Herbert et al 2011;Lyvers et al 2014). Furthermore, individuals with alexithymia experience less pleasure during relaxation and report more boredom, with suggestions they may find it difficult to engage with and derive pleasure from the stimulation in their environment (Eastwood et al 2007;Eastwood et al 2012;Friedlander et al 1997). Low sensory registration has also been reported in individuals with ASD (Crane et al 2009;De la Marche et al 2012); therefore our findings suggest that there is an overlap in sensory modulation difficulties between the two conditions.…”
Section: The Association Between Alexithymia and Sensory Sensitivitiesmentioning
confidence: 99%
“…This is reflected in findings of poorer bodyperception, such as reduced registration of the effects of chemical intake or poorer perception of own heart beat (Ernst et al 2014;Herbert et al 2011;Lyvers et al 2014). Furthermore, individuals with alexithymia experience less pleasure during relaxation and report more boredom, with suggestions they may find it difficult to engage with and derive pleasure from the stimulation in their environment (Eastwood et al 2007;Eastwood et al 2012;Friedlander et al 1997). Low sensory registration has also been reported in individuals with ASD (Crane et al 2009;De la Marche et al 2012); therefore our findings suggest that there is an overlap in sensory modulation difficulties between the two conditions.…”
Section: The Association Between Alexithymia and Sensory Sensitivitiesmentioning
confidence: 99%
“…A number of studies have found that alexithymia is related to higher levels of resting (tonic) sympathetic or cardiovascular activity (Friedlander, Lumley, Farchione, & Doyal, 1997;Fukunishi, Sei, Morita, & Rahe, 1999;Gundel et al, 2002;Henry et al, 1992;Infrasca, 1997;Stone & Nielson, 2001;Wehmer, Brejnak, Lumley, & Stettner, 1995), although other studies have found no alexithymia effect on resting measures (Luminet, Rimé, Bagby, & Taylor, 2004;Newton & Contrada, 1994;Roedema & Simons, 1999;Waldstein, Kauhanen, Neumann, & Katzel, 2002). No studies, however, have shown that alexithymia is associated with lower resting physiological activity.…”
Section: Does Alexithymia Contribute To the Etiology Or Pathology Of mentioning
confidence: 99%
“…The following symptoms of alexithymia are mentioned in the literature (Abe & Izard, 1999;Apfel & Sifneos, 1979;Berenbaum & Irvin, 1996;Berenbaum & Prince, 1994;Dewaraja, Tanigawa, Araki, Nakata, Kawamura, Ago & Sasaki, 1997;Friedlander, Lumley, Farchione, & Doyal 1997;Izard, 1990;Kauhanen, Kaplan, Cohen, Salonen, & Salonen, 1994;King, 1998;King & Emmons, 1990;Kooiman, 1998;Lane & Schwartz, 1987;Lane, Ahern, Schwartz & Kaszniak, 1997;Lane, Sechrest, Reidel, Weldon, Kaszniak, Schwartz, 1996;Taylor, Bagby, & Parker, 1997). On the physical level the individual shows a decreased immune response, a variety of ailments such as hypertension and a decrease in ability to associate physical sensations with emotions.…”
Section: Alexithymiamentioning
confidence: 99%